Pengaruh Senam Hamil, Pemberian Modul Senam Hamil dan Cara Tidur yang Baik Terhadap Durasi Tidur pada Ibu Hamil Trimester III di Puskesmas Saumlaki - Dwi Wahyunita, Vina; Anthonete Salakory, Jacomina; Anthoineta Sahertian, Betty (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The increasing age of pregnancy accompanied by anatomical changes causes complaints of sleep disturbances due to discomfort such as back pain, frequent urination, fetal movements, fatigue, and difficulty initiating sleep. Prenatal exercises help the body produce more endorphins, providing calmness, managing stress, and regulating sleep positions to make sleep more comfortable. The research aims to analyze the influence of prenatal exercises, the provision of modules, and good sleeping positions on the duration of sleep for pregnant women in the third trimester at the Saumlaki Health Center. The research design is Quasi-Experimental with a pretest-posttest control design, sampling 30 respondents in each group, using the Mann Whitney test. The results show that the average duration of sleep for pregnant women given modules, prenatal exercises, and good sleeping positions (8.80 hours), with a higher mean rank (39.67) compared to pregnant women who walk in the morning and sleep normally (21.33). It is concluded that there is an influence of prenatal exercises, the provision of modules, and good sleeping positions on the duration of sleep for pregnant women. Sleep disturbances during pregnancy should not be taken lightly because if left untreated, they pose risks to both the mother and the fetus.